The Effect of Fiction vs Nonfiction in the Digital Era: Text Comprehension not Influenced by Genre Expectations. Issue 10 (26th November 2021) - Triantafyllopoulos, Maria; Li, Binyan; Schnabel, Margaret; Breithaupt, Fritz
ABSTRACT: Do people comprehend texts differently based on genre expectation, i.e. whether they are instructed to read a text as fiction or nonfiction? In earlier studies conducted before the prevalence of digital and online reading, texts labeled as nonfiction demonstrated greater situational-model comprehension (gist), while the same text labeled as fiction demonstrated greater surface-level comprehension (word memory). Here we report three online experiments that examine the influence of genre expectations on comprehension today. In none of our studies do we record a difference in text comprehension based on genre expectation. We also collected data on self-reported reading habits and our analyses of these data do not show that individual prevalence of online reading directly moderates effects of genre expectations. Nevertheless, overall, the genres of fiction and nonfiction do not appear to exert universal effects on reading comprehension, especially in the world of digital and online reading.